Paradigm of Legal Thought: Legal Prophetic Perspective - Fitrah Hamdani (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Objective: This article aims to discuss ‘criticism of legal prophetic paradigm against legal positivism paradigmMethodology: This research conducted a normative method used by legal positivists. This research is based on a philosophical approach as it is intended to explore the basic assumptions of the legal prophetic paradigm on the lack of the basic assumptions of the legal positivism paradigm.Findings: This paper will discuss the 'criticism of legal prophetic paradigm against legal positivism paradigm' using a philosophical approach as it is intended to explore the basic assumptions of the epistemology basis of the school of thought in legal science through comparison between the school of thoughts in legal science. The legal prophetic paradigm places moral as the main basis as its basic assumption. The verses of Allah and the Hadith of the Prophet regarding justice are the ontological basis of the Paradigm.Application of the Study: The object of legal science is human relations contained within (governed by) legal norms. Law science attempts to understand its object in a